Early sport dropout: High performance in early years in young athletes is not related with later success (Abandono deportivo precoz: el alto rendimiento en edades tempranas no garantiza el éxito deportivo en la edad adulta) - Latorre-Román, Pedro Ángel; Garcia Pinillos, Felipe; López Robles, Juan (Retos, 2018)
Abstract. Objective: to analyze the career (based on the Royal Spanish Athletics Federation (RFEA) rankings) and/or dropout rates of the top 10 athletes aged14 to 19 years, during the period 2004-2014. Equipment and methods: Top 10 finishers in different athletic disciplines in the time range from 2004 to 2014 were selected after consulting the yearly national ranking database of the RFEA, published on its website (www.rfea.es). Results: There were 1,144 participants, 594 males and 550 females. All athletes, at the time of their presence in the top 10 in 2004, were between 14-19 years old, belonging to the following categories: cadet (14-15 years), youth (16-17 years) and juniors (19-19 years), in both sexes. There was a significant reduction of athletes in the top 10 from 2004 to 2014. Of the 1,144 athletes taken into consideration in 2004, 1,104 (96.50%) were considered as dropouts from high performance in 2014: 543 (98.72%) were women, and 561 (94.45%) were men. From the overall analysis and taking into account the athletic disciplines, sprint and hurdles in males (99.4%), and middle/long running and walks in females (100%), showed the highest percentage of dropouts. These results oppose the idea that success at a young age (i.e., the top 10 ranking) ensures later success. Therefore, in athletics where peak performance is achieved close to the senior category, early specialization should be questioned. Resumen. Objetivo: analizar la carrera deportiva (basándonos en los rankings reportados por la Real Federación Española de Atletismo - RFEA) y las tasas de abandono de los atletas encuadrados en el top 10, con una edad entre 14-19 años, entre los años 2004 a 2014. Método: basándonos en la base de datos aportada por la RFEA a través de su web (www.rfea.es) desde 2004, han sido seleccionados el top 10 en diferentes disciplinas atléticos entre los años 2004-2014. Resultados: participaron 1144 participantes, 594 varones y 550 mujeres. Todos los atletas, en el momento de su presencia en el top 10 en 2004 tenían entre 14-19 años, y pertenecían a las categorías: cadetes (14-15 años), juvenil (16-17 años) y junior (18-19 años) en ambos sexos. Se halló una reducción significativa de atletas presentes en el top 10, entre 2004-2014. De los 1144 atletas considerados en 2004, 1104 (96.50%) abandonaron el top10 en 2014: 543 (98.72%) fueron mujeres, y 561 (94.45%) hombres. Considerando las disciplinas atléticas, las pruebas de sprint y vallas (99.4%) y la carrera de medio fondo y marcha en mujeres (100%) mostraron la mayor tasa de abandono. Conclusión: estos resultados muestran que el éxito a edades jóvenes no asegura el rendimiento en etapas posteriores del desarrollo. Por tanto, en disciplinas deportivas en las que el pico de rendimiento se alcanza a edad adulta, la especialización precoz se debe poner en duda.